Boosting learning achievement in physics among Ugandan form-2 students: effect of problem-based learning - Gumisirizah, Nicholus; Muwonge, Charles M; Nzabahimana, Joseph (Physics Education, 2023)
Enabling students to learn smoothly at an early stage of learning is a paramount effort that African education should takeoff. This study established the effect of problem-based learning (PBL) on students’ learning achievement. The participants were selected from form-2 of lower secondary schools in Sheema District, Western Uganda. Participants were randomly assigned to the treatment class with PBL instruction and the control class with content-based learning (CBL). A quantitative approach and a quasi-experimental design were used. Thus, the pretest-posttest non-equivalent quasi-experimental design was applied. A learning achievement test in simple machines was used as a data collection tool. The test was validated by experts and piloted with a split-half reliability (r = 0.87). Data was analysed in MS Excel and SPSS. A repeated measures analysis of variance revealed a very high statistically significant difference (p < .001) after learning in both classes. The same significance was found between PBL and CBL in favour of PBL. Classical test theory was used to present item difficulty and discrimination index. Teachers were recommended to adopt these methods with more practical hands-on activities to boost their skills and conceptual understanding.
Keywords: Content-based learning; Form-2 Ugandan secondary school; Physics problem-based learning; Simple machines; Students’ learning achievement